Does financial development improve human capital accumulation in the Southeast Asian countries? - Duc Hong Vo; Ngoc Phu Tran; Ha Minh Nguyen (Cogent Business & Management, 2021)
Financial development and human capital's crucial roles in economic growth have been widely recognized in the literature. However, a direct link between financial development and human capital, in the long run, has not been investigated, in particular in emerging markets in Asia. This study investigates the nexus between financial development and human capital for a group of nine emerging markets in the Southeast Asian region over the period 1990-2018. Econometric techniques allowing for cross-sectional dependence and panel co-integration, such as the dynamic least squares (DOLS) and fully modified least squares (FMOLS), are used. We also use three indicators as the proxies for financial development: broad money supply, bank credit, and private sector credit. Empirical findings from this paper indicate that financial development contributes positively and significantly to human capital accumulation. We also find that economic growth enhances the formation of human capital. Results from our Granger causality tests confirm a bi-directional relationship between financial development and human capital. Policymakers from the Southeast Asian emerging markets may need to enhance and extend financial development which is closely linked with human capital accumulation.
Keywords: 650; Financial development; economic growth; Human capital; FMOLS; DOLS; Asian emerging markets